Le gentleman kiplingien dans tous ses états : audaces de « The Man Who Would Be King » - Gilbert Pham-Thanh (Cahiers Victoriens et Edouardiens)
This article deals with « The Man Who Would Be King », a short story by Rudyard Kipling which introduces English characters into exotic settings where their ability to prove bold and daring is of the essence. Through the diegetic itinerary of these representatives of masculinity, the theme of adventure is made symbolic on several grounds. In particular, it enables the author to question the social order of the motherland, to criticize the colonial process and to expose the staged procedures of validation of masculinity. This will be shown to disqualify the English subject’s pretention to embody the dominant male.